Targeting Upstream Kinases of STAT3 in Human Medulloblastoma Cells - Wei, Jia; Ma, Ling; Li, Chenglong; Pierson, Christopher R.; Finlay, Jonathan L.; Lin, Jiayuh (Current Cancer Drug Targets, 2019)
Background: Medulloblastoma is the most common malignant brain tumor in children. Despite improvement in overall survival rate, it still lacks an effective targeted treatment strategy. The Janus family of cytoplasmic tyrosine kinases (JAKs) and Src kinases, upstream protein kinases of signal transducer and activator of transcription 3 (STAT3), play important roles in medulloblastoma pathogenesis and therefore represent potential therapeutic targets. Methods: In this report, we examined the inhibitory efficacy of the JAK1/2 inhibitor, ruxolitinib, the JAK3 inhibitor, tofacitinib and two Src inhibitors, KX2-391 and dasatinib. Results: These small molecule drugs significantly reduce cell viability and inhibit cell migration and colony formation in human medulloblastoma cells in vitro. Src inhibitors have more potent efficacy than JAK inhibitors in inhibiting medulloblastoma cell migration ability. The Src inhibitors can inhibit both phosphorylation of STAT3 and Src while JAK inhibitors reduce JAK/STAT3 phosphorylation. We also investigated the combined effect of the Src inhibitor, dasatinib with cisplatin. The results show that dasatinib exerts synergistic effects with cisplatin in human medulloblastoma cells through the inhibition of STAT3 and Src. Conclusion: Our results suggest that the small molecule inhibitors of STAT3 upstream kinases, ruxolitinib, tofacitinib, KX2-391, and dasatinib could be novel and attractive candidate drugs for the treatment of human medulloblastoma.
Keywords: dasatinib